The model of international relations in the Baltic Sea region: political shifts and current challenges - Zhukovsky I. I. (Baltic Region)
The demise of the USSR and the revision of the Yalta-Potsdam system of international relations led to tectonic changes in the Baltic Sea region: it became apparent that the northern flank, once the most likely battleground between the North Atlantic Alliance and the Warsaw Pact, had a historical opportunity to transform into a region of intensive political, economic, educational and cultural interaction. Under these circumstances, the construction of a new regional system of international relations unfolded at the turn of the 20th and 21st centuries. This article examines the evolution of the regional model of international relations, from a ‘cohesion region’ to a modern ‘conflict region’, through the analysis of the dynamics of regional cooperation networks amidst the crisis in the international system and politics. The study builds on the tradition of historical and political analysis of regions as agents in the international relations system, drawing on relevant documents and materials from international organisations, foreign ministries and other authorities of the Baltic Sea region states. The final part of the research emphasises the need for experts to search for a post-conflict regional agenda, with some proposals outlined.